Effects of resistance training periodization on performance and salivary immune-endocrine responses of elite female basketball players - Nunes, J. A.; Crewther, B. T.; Viveiros, L.; de Rose, D.; Aoki, M. S. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM:The aim of this paper was to examine the effects of resistance training periodization on the performance and salivary hormone-immune responses of elite female basketball players. METHODS: Twelve female athletes were monitored across a 50 day period of resistance training that emphasized strength, endurance and power. One repetition maximum (1RM) strength, maximal repetitions at 50% 1RM and vertical jump performance was assessed pre- and post-training. Saliva samples were also collected at 0700, 0930, 1100 and 1730 hours and analyzed for testosterone (T), cortisol (C) and immunoglobulin A (IgA). RESULTS: Improvements in 1RM strength, maximal repetitions and vertical jump performance were identified post-training (P<0.05). Training had no effect on salivary T and C concentrations, but the T:C ratio increased at 0730 hours (P<0.05) and IgA concentrations were lowered at 0930 and 1100 hours (P<0.05). The changes (Pre-Post training) in strength and T concentrations were positively correlated at 0730 hours (P<0.05). CONCLUSION: A periodized approach to resistance training increased muscle performance in elite female basketball players, but only minor changes in the salivary T:C ratio and IgA were noted. Correlational analysis identified a possible role for early morning changes in T as a regulator of individual strength changes.